Efektivitas Iklan Dalam Membentuk Perilaku Pembelian Produk Hijau Melalui Peran Mediasi Sikap Pada Mahasiswa di Kota Palembang - Wangsa, Ignasius Heri Satrya; Lina (BIP's JURNAL BISNIS PERSPEKTIF, 2025)
This study aims to analyze the effectiveness of advertising in shaping green product purchasing behavior through the mediating role of consumer attitudes. Referring to the Theory of Planned Behavior and Signaling Theory, this study highlights two main aspects of advertising—exposure and credibility—in influencing consumer decisions towards environmentally friendly products. The study uses a quantitative approach with the Structural Equation Modeling - Partial Least Squares (SEM-PLS) analysis technique, based on data from 55 student respondents aged 18–24 years in Palembang City, Indonesia. The results show that advertising credibility has a significant effect on consumer attitudes, which then influence green product purchasing behavior. Conversely, advertising exposure has a direct effect on purchasing behavior, but does not significantly shape attitudes. Attitude is proven to be a significant mediator between advertising credibility and green product purchases, but does not act as a mediator between advertising exposure and purchases. These findings emphasize the importance of building trust through credible advertising, rather than relying solely on the frequency of exposure. In the context of green marketing, message credibility plays a key role in shaping positive consumer attitudes that drive sustainable purchasing behavior. In practice, marketers need to emphasize transparency, authenticity, and concrete evidence in delivering green advertising. The study also recommends further exploration of other psychological or demographic factors that can strengthen the effectiveness of green marketing communication strategies across consumer segments.